Classical philology and theology : entanglement, disavowal, and the godlike scholar - Conybeare, Catherine; Conybeare, Catherine; Goldhill, Simon; Goldhill, Simon (Cambridge University Press, 2020)
Cover -- Half-title page -- Title page -- Copyright page -- Contents -- List of Contributors -- Chapter 1 Philology's Shadow -- Chapter 2 Philology's Roommate: Hermeneutics, Antiquity, and the Seminar -- Chapter 3 The Union and Divorce of Classical Philology and Theology -- Chapter 4 The Philology of Judaism: Zacharias Frankel, the Septuagint, and the Jewish Study of Ancient Greek in the Nineteenth Century -- Chapter 5 Source, Original, and Authenticity between Philology and Theology -- Chapter 6 Whose Handmaiden? 'Hellenisation' between Philology and Theology -- Chapter 7 Julian the Emperor on Statues (of Himself) -- Chapter 8 Boethius in the Genres of the Book: Philology, Theology, Codicology -- Chapter 9 Virgil, Creator of the World -- Chapter 10 Theology's Shadow -- Bibliography -- Index.